Vicente Mira, Pilar Ruiz, Carmen Gallano (eds.). Conceptos freudianos. Madrid: Síntesis, 2005. (Cuestiones de Género: de la igualdad y la diferencia, 2006)
Conceptos freudianos.Vicente Mira, Pilar Ruiz, Carmen Gallano (eds.).Madrid: Síntesis, 2005.